Duct Luschka: an anatomic variation of biliary tree detected during cholecystectomy - Fonseca Neto, Olival Cirilo Lucena da; Martins, Beatriz Costa Nava; Pedrosa , Maria das Graças Lapenda (Revista de Medicina, 2023)
The Luschka duct is an anatomical alteration that is not easily identified in the preoperative imaging exams. Knowledge of the anatomy and the possibility of finding this anatomical structure provides greater safety in the surgical procedure. The case described addresses an intraoperative biliary leak due to the presence of the Luschka duct during an open cholecystectomy and its management. Objective: To describe the case of a patient with cholelithiasis, submitted to a conventional cholecystectomy in an elective manner, in which the presence of the Luschka duct was detected intraoperatively, as well as the surgical and clinical management of the case. Result: The patient underwent cavitation drainage intraoperatively, as well as duct ligation. She presented good evolution in the following days, with clinical improvement, and was discharged from the hospital in good condition on the 4th postoperative day. Discussion: The Luschka duct is one of the most common anatomical variations of the biliary tree. The identification of this duct in the preoperative period is extremely difficult and rare, and its surgical treatment usually consists of lavage of the abdominal cavity, closure of the Luschka duct and intraoperative cholangiography to confirm that the biliary tree is intact. Conclusion: The importance of knowledge and surgical and clinical management of this anatomical structure is important for a good evolution of the patient.